Nanostructured Polymer Fibers with Enhanced Adhesion to Epoxy Matrices. Issue 3 (5th November 2012) - Fernández‐Blázquez, Juan P.; Setzer, Sandro; del Campo, Aránzazu
Abstract A method for reinforcing the strength of the interface between a polymer fiber and a polymer matrix is described. PET fibers were etched in an oxidative plasma to generate a surface nanopattern. Depending on the plasma treatment time, lamellae patterns with different geometries were obtained. The interfacial shear strength (IFSS) between the fiber and a epoxy matrix was measured for the different surface topographies. A twofold increase in the IFSS was obtained for lamellae with 100 nm thickness, 300 nm height, and separated by 400 nm valleys. Our results demonstrate the benefit of a surface pattern for reinforcing the interface between fibers and resin. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>